Pharmacokinetics and Pharmacodynamics of Ulipristal Acetate in Fibroid Treatment - Fatima Usama, Syeda Madiha Tahir, Aisha Aslam, Noreen Tahir, Shazia Bibi, Naureen Ghani, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: The selective progesterone receptor modulator Ulipristal Acetate works as a medicinal treatment for symptomatic uterine fibroid management. The medical treatment provides surgical procedure alternatives through fibroid reduction and regulation of irregular menstruation. A goal of this research was to examine how UPA behaves when treating fibroids both pharmaceutically and dynamically. Methodology: The 12-month prospective research took place at Kuwait Teaching Hospital, Peshawar. The research included 94 patients who qualified with symptomatic uterine fibroids. Each patient received 5 mg of UPA daily for 12 weeks. The pharmacokinetic evaluation used serial blood sampling to determine both the maximum concentration of drug reached (C-max) and time to reach maximum concentration (T-max) and area under the curve (AUC) as well as the elimination half-life. The study evaluated the pharmacodynamic results which included reducing fibroid volumes as well as blocking ovulation and managing menstrual bleeding. The evaluation used paired t-tests together with ANOVA and Pearson’s correlation tests at a p value cutoff of 0.05. Results: During 12 weeks of UPA therapy patients experienced a fibroid volume reduction of 36.6% (p < 0.001) and ovulation suppression reached 92.5% of participants which led to menstrual bleeding control in 81.9% of patients. The analyzed pharmacokinetic data showed C-max levels at 42.5 ± 5.8 ng/mL which occurred at T-max at 1.8 ± 0.6 hours following an elimination half-life of 37.6 ± 4.2 hours. Women in the study showed declining serum estradiol levels down to 42.1 ± 8.9 pg/mL which stayed within normal mid-follicular phase ranges. Most patients only experienced brief side effects including headache and nausea according to records thatTMP UPA produced. Conclusion: Use of UPA produced effective fibroid reduction that also controlled menorrhagia while inhibiting menstruation alongside beneficial drug metabolism and minimal adverse effects. The collected data indicates that UPA functions as an efficient non-procedural therapy for dealing with uterine fibroids. The ongoing safety and recurrence patterns of treated fibroids should be investigated through future research after medication cessation. Keywords: Ulipristal Acetate, Uterine Fibroids, Pharmacokinetics, Pharmacodynamics, Menstrual Bleeding Control, Ovulation Suppression, Non-Surgical Treatment